[3-({(E)-2-[(4-Fluorophenyl)carbamothioyl]hydrazinylidene}methyl) -4-hydroxybenzyl]methyltriphenylphosphonium chloride - Tan, Kong Wai; Tiekink, E.R.T.; Sinniah, S.K.; Ng, S.W.; Sim, K.S. (International Union of Crystallography, 2011)
The cation in the title salt, C 33H 28FN 3OPS +·Cl -, is highly twisted with the phospho-nium group occupying a position almost normal to the central hydroxyl-benzene ring [P - C - C - C tosrsion angle = -100.9 (3)°], and with the hydrazone substituent twisted out of the plane [C - C - C - N torsion angle = 13.1 (4)°]. The fluoro-benzene ring is twisted out of the plane of the adjacent thio-urea residue, forming a dihedral angle of 51.69 (10)°. The configuration about the C=N bond [1.281 (4) Å] is E, the O - H and N - H hydrogen atoms are syn, and in the thio-urea residue, the N - H hydrogen atoms are anti, allowing for the formation of an intramolecular N - H⋯N hydrogen bond. In the crystal, dimeric aggregates mediated by N - H⋯S bonds are formed, which are linked to the Cl - anions by O-H⋯Cl hydrogen bonds. The four-component aggregates are linked into a three-dimensional structure by C - H⋯Cl interactions.